A qualitative analysis of female sex workers’ lived experiences with adherence to Pre-exposure Prophylaxis (PrEP) in Zimbabwe - Definate Nhamo; Dixon Chibanda; Frances M. Cowan; Sinegugu E. Duma (PLoS ONE, 2025)
Background Female sex workers (FSWs) are at an elevated risk of HIV infection with an eight-fold risk of HIV infection. In countries like Zimbabwe, FSWs have an HIV incidence of around 10.2%. With this elevated risk, the World Health Organization has prioritized Female sex workers (FSWS) for PrEP – an HIV prevention option taken as a daily pill during periods of risk but, FSWs continue to experience challenges with daily PrEP adherence due to daily dosing, related side effects, ARV stigma and low risk perception. This article presents the FSWs’ lived experiences with PrEP adherence in Zimbabwe. Methods We purposively identified twenty FSWs and conducted individual interviews to understand FSW lived experiences with PrEP adherence. We applied Colaizzi’s seven steps of phenomenological analysis to develop the themes. Findings Three main themes emerged, namely positive experiences with PrEP adherence, negative experiences with PrEP adherence and the meaning attached to PrEP adherence. The positive experiences theme had four sub-themes as, overcoming PrEP-related forgetfulness, overcoming mobility-related PrEP disruptions, overcoming COVID-19 pandemic-related PrEP experiences and overcoming PrEP-related side effects. The negative experiences theme had two sub-themes including, enduring GBV and stigma associated with PrEP use and, COVID-19-related disruptions to PrEP adherence. The third emerging them was on the meaning attached to PrEP adherence. This theme had one sub-theme on PrEP adherence as a survival strategy. Conclusion Whilst FSWs reported both positive and negative experiences with PrEP adherence, it is important that FSWs used the meaning they attached to these experiences to take control of their lives and be more determined to use PrEP adherence for survival and protection from HIV. Based on these findings, we recommend close monitoring and support to promote adherence, minimize PrEP discontinuity and promote positive lived experiences with PrEP adherence.